Myeloperoxidase anti‐neutrophil cytoplasmic antibody affinity is associated with the formation of neutrophil extracellular traps in the kidney and vasculitis activity in myeloperoxidase anti‐neutrophil cytoplasmic antibody‐associated microscopic polyangiitis - Yoshida, Masaharu (Nephrology (Carlton), 2016)
Anti‐neutrophil cytoplasmic antibody (ANCA) is associated with small‐vessel vasculitis particularly in the kidneys and can induce the formation of neutrophil extracellular traps (NETs) from primed neutrophils. Recently we have reported that the induction of NETs correlates with ANCA affinity for myeloperoxidase (MPO) and disease activity in patients with MPO‐ANCA‐associated microscopic polyangiitis. To investigate whether MPO‐ANCA affinity is associated with the formation of NETs in vivo, we examined the occurrence of NETs in the renal tissues of patients with MPO‐ANCA‐associated microscopic polyangiitis and ANCA affinity by double immunofluorescence staining for NET components of citrullinated histone, MPO and PAD4 and by ELISA competition with MPO, respectively. We divided 30 MPO‐ANCA‐associated microscopic polyangiitis patients into 2 groups based on their ANCA affinity levels (IC(50) for the high: 0.11 ± 0.04 µg/mL (Group1) and IC(50) for the low: 0.66 ± 0.24 µg/mL (Group2)). Group1 showed a higher Birmingham vasculitis activity score (15.6 ± 5.7) and 73% of the patients presented clinically with rapidly progressive glomerulonephritis and histologically with focal/crescentic glomerulonephritis (GN). Group 2 showed a lower Birmingham vasculitis activity score (9.2 ± 4.9) and 73% of the patients presented clinically with chronic renal failure and histologically with mixed/sclerotic GN. Group 1 showed a much higher occurrence of NETs than Group 2. Our findings indicate that ANCA affinity was associated with the in vivo formation of NETs, which might be involved in the pathophysiology of patients with MPO‐ANCA‐associated microscopic polyangiitis.